2015
DOI: 10.1007/s10029-015-1407-0
|View full text |Cite
|
Sign up to set email alerts
|

An international surgical collaboration: humanitarian surgery in Brazil

Abstract: The humanitarian mission provided hernia surgery to an underserved population in Brazil and training to local doctors, building local sustainability. Continued cooperation between host and international surgeons for future missions to Brazil will ensure continuing surgical training and technical assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Numerous studies deliberated the charity healthcare providers through different specialties and performances. [10][11][12][13][14][15] Besides, the pharmacist contributed to charity pharmaceutical services with various types of performances, counting clinical pharmacy activities. [16][17][18][19][20] The local study showed that healthcare providers participate as volunteer jobs through the mass gathering medicine Hajj period.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies deliberated the charity healthcare providers through different specialties and performances. [10][11][12][13][14][15] Besides, the pharmacist contributed to charity pharmaceutical services with various types of performances, counting clinical pharmacy activities. [16][17][18][19][20] The local study showed that healthcare providers participate as volunteer jobs through the mass gathering medicine Hajj period.…”
Section: Introductionmentioning
confidence: 99%
“…Similar missions to Haiti and Brazil have provided surgical services to underserved populations by training local doctors and building local sustainability [17,18]. Also, several institutions have reported successful global health initiatives for surgical residents and faculty which were effectively integrated into academic surgical residency programs through relationships with training programs in low-income countries [6].…”
mentioning
confidence: 99%